Fever of unknown origin in childhood: difficulties in diagnosis. - Martin, K (1994)
We have described a child with systemic onset juvenile chronic arthritis who presented initially with fever of unknown origin. Treatment of a presumed infection led to a severe allergic response with Stevens-Johnson syndrome, renal failure and DIC. This reaction obscured the features of the underlying disease and delayed the diagnosis.